A Literature Review: Prevention of a Growing Pandemic, Middle Eastern Respiratory Syndrome - Saleh, Sherif (My University, 2015)
Background: Middle Eastern Respiratory Syndrome is a viral respiratory syndrome caused by MERS-CoV. From its first identification in 2012 until today, 1,374 laboratory-confirmed cases of infection with MERS-CoV have been identified in 26 countries, with the majority of these cases (>80%) occurring in the Kingdom of Saudi Arabia (KSA). The rapid international spread of this virus suggests that it is crucial to review the current prevention & control strategies. It is also important to outline further recommendations to prevent the growth of a potential pandemic disease. Methodology: This study was conducted as a targeted literature review and critical analysis of articles from multiple databases. An emphasis was put on the updates and archives posted by the WHO – coronavirus infections. Prevention Strategies: Researchers have studied the rapid spread of MERS-CoV in KSA, focusing on viral spread in hospital settings, via dromedary camels, and religious mass gatherings as risk factors. Current advancements in the knowledge of camels as a potential MERS reservoir, guidelines for travelers to high-risk countries, and improvements in the surveillance have contributed to the reduction of the MERS incidence cases globally. Despite these prevention strategies, more outbreaks continue in KSA and major recent outbreaks have been reported in the Republic of Korea. Conclusion: The remaining and ongoing MERS cases reported in KSA & Republic of Korea represent a global public health concern. As a result there is a need to further improve the management of MERS. Given the rapid spread of the virus and the gap in literature about the transmission of MERS, it is recommended that both high and low risk nations abide by the international MERS recommendations outlined by the WHO. Furthermore, collaboration between the animal and human public health organizations would serve as a progressive step to control the spread of this zoonotic disease.
This paper provides an update of the epidemiological trends of MERS globally. With a focus on current prevention and control strategies taken by the Ministry of Health in the Kingdom of Saudi Arabia, the paper outlines a few recommendations to prevent the spread of a pandemic threat.
Keywords: Infectious Disease; Middle Eastern Respiratory Syndrome; Prevention and Control; Kingdom of Saudi Arabia; MERS-CoV; Epidemiological Update